The Effectiveness of Using Indonesian Language as A Communication Media between Baduy Communities and Tourists - Lina Marliana Dewi (Pusat Riset dan Inovasi Nasional, 2023)
This study aims to determine the effectiveness of using Indonesian in building Baduy communication with intercultural tourists. This study uses the research method used is qualitative research based on the philosophy of postpositivism, used to examine the condition of natural objects. The instruments used in this study were observations, interviews, field notes and documentation. The data collected is by interview technique. Based on the analysis conducted, it was found that the Baduy people can speak Indonesian and use Indonesian to communicate with tourists. Apart from that, we also analyze that the Baduy people learn Indonesian from their parents and tourists because they don't go to school. The effectiveness of using Indonesian makes the communication that exists between the Baduy people and tourists run smoothly and better. In this study, researchers tried to interact with 9 Baduy people and 7 of them stated that almost 20% were fluent in Indonesian, 50% could speak Indonesian but were not fluent and 30% of the Baduy people passively used Indonesian. Based on the results of data analysis, it can be seen that approximately 70% of the Baduy people can use Indonesian well and can interact fluently with tourists or outsiders. As explained above, being said to be effective means successfully conveying the message each speaker raises. This can make it easier to communicate and interact easily with outsiders besides the Baduy because not all tourists can use the native language of the Baduy tribe, namely Sundanese. With the effective use of Indonesian it is very clear that it can help to communicate easily and fluently.